The Effectiveness of the Use of Digital Marketing and Green Products in Improving Purchase Decisions at Mcdonald's Pancing - susilo, Stevany; Elisabeth Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to find out how much digital marketing and green product influence the purchase decision at Mcdonald's Pancing. The research methodology used is a quantitative descriptive method. The population in this study is consumers of Mcdonald's Pancing. The technique for determining the number of samples used in this study is the Hair formula. The results of the analysis provide the equation Purchase Decision = 10.831 + 0.580 Digital Marketing + 0.654 Green Product + e. The results of t test on this study show that the variables of digital marketing and green product also partially have a positive and significant effect on purchasing decisions at Mcdonald's Pancing. The results of the F test also show that the independent variables (digital marketing and green product) simultaneously affect the bound variable (purchase decision). The result of the determination coefficient (R2) test showed that 56.8% of the consumer satisfaction variables were influenced by digital marketing and green products while the remaining 43.2% were influenced by other variables.